Strategy for Developing Dairy Farming for All-Business Cooperatives in Tandangsari, Sumedang Regency - Sumaryana, Fitriana Dewi; Putra, Toufiq Agung Pratomo Sugito; Hakim, Abdul; Rahmat, Aina Athifa (International Journal of Business, Economics, and Social Development, 2023)
The livestock sector has proven itself to be a crisis-resistant sector. The Ministry of Agriculture stated that the total national milk demand in 2019 reached 4,332.88 thousand tons. One of the dairy cattle center areas that has developed and become the focus of the Sumedang Regency Government is Tanjungsari District. The breeders joined the Tandangsari KSU. The supply and demand for pure milk has fluctuated at KSU Tandangsari in the last five years. The problems in the dairy cattle business at KSU Tanjungsari are currently related to production factors as inputs in the development of a dairy cattle business including livestock seeds, feed availability, land as living space for livestock, livestock production facilities (procurement of equipment and maintenance of livestock production), labor (breeders), as well as the cost of production.The goal of preparing the RIP is to formulate alternative strategies for developing a dairy cattle business. By identifying strengths and weaknesses, as well as opportunities and threats based on internal and external factors that affect the dairy cattle business at KSU Tandangsari.The strategy for developing a dairy cattle business is the S-O (1) strategy. Development of cattle population to increase production, (2). Building a place (factory) for processing dairy products, W-O strategy (1). Build a cow nursery, (2). Establishing cooperation with third parties in producing processed HPT, strategy S-T (1). Increasing the quality and quantity of beef cattle, (2). Moving the location of the fresh milk business activity center (MCU), W-T strategy (1). The application of appropriate technology is increased by breeders, (2). Establish cooperation with financial institutions in capital facilities.